IDENTIFICATION OF ACTIVE COMPOUNDS AND FORMULATION AS AN ANTISEPTIC MOUTHWASH FROM THE PLANT Cassia fistula L. AS A PREVENTIVE MEASURE AGAINST DENTAL AND ORAL DISEASES CAUSED BY THE BACTERIA Enterococcus faecalis - Romundza, Febbry; Harizon, Harizon (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
A compound with the molecular formula C15H24O has been identified as Caryophyllenol-II through analysis using HR-TOF-MS, IR, and NMR spectroscopy. The Â¹Â³C-NMR spectrum indicates that this compound is a bicyclic sesquiterpenoid, characterized mainly by the presence of a hydroxyl group replacing an epoxide ring and the addition of an olefinic bond. The relationship between the compounds analyzed from Cassia fistula L. and their antibacterial activity against Enterococcus faecalis can be explained through the identification of bioactive compounds with specific mechanisms to inhibit or kill the bacteria. Compounds from Cassia fistula L. have significant potential as an antibacterial agent against Enterococcus faecalis, particularly through membrane disruption and bacterial enzyme inhibition mechanisms. Further research on their role, either individually or in combination with other compounds, could support the development of C. fistula-based antiseptic products, such as mouthwash, for the prevention and treatment of oral and dental diseases. Additionally, this research explores the antibacterial potential of Cassia fistula L. in developing an antiseptic mouthwash. Extracts from Cassia fistula L. are known to contain active compounds such as flavonoids, alkaloids, and tannins, which demonstrate effectiveness against Enterococcus faecalis, as a primary cause of dental and oral infections. The mouthwash formulation based on this extract was tested in vitro and proposed as a natural and safer alternative compared to synthetic chemical-based products for the prevention of dental and oral infections. This study indicates the significant potential of Cassia fistula L. in supporting oral health through effective antiseptic products. These findings support the use of traditional medicinal plants like Cassia fistula L. as a source of active compounds for the development of effective natural antiseptics and have the potential to reduce dependence on synthetic antiseptics while also promoting economic empowerment through simple industries.